Perancangan Antarmuka Pengguna Aplikasi Sistem Informasi Siswa berbasis Android menggunakan Metode User Centered Design (Studi pada : di SMK Telkom Banjarbaru) - Atika Shinta Pratiwi; Satrio Hadi Wijoyo; Satrio Agung Wicaksono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The emergence of the COVID-19 pandemic has made learning to be carried out online. SMK Telkom Banjarbaru is one of the schools that conducts online learning, so teachers or educators only get information through communication media (mobile phones), and information from parents as supervisors for learning at home. Learning is carried out smoothly but there is one obstacle in learning at SMK Telkom Banjarbaru is the lack of information to find out student activities by teachers and parents. One solution is to design an android-based application for student information systems using the User Centered Design (UCD) method. This method focuses on user needs, in this design it is classified into students, teachers, and homeroom teachers. In the final stage of this research, namely testing on the application design, all users can achieve task scenarios in each role with a success percentage of 100% so that the application design can be easily recognized and used.